Philoctetes and the Good Companion Story (ENTHYMEMA, 2016)
The idea of a companion story is developed through an analysis of Sophocles’ play Philoctetes, about living in chronic pain. That story is anchored by an ethnographic report of a boy living with pain, and his companion story. The good companion story is distinguished by three qualities: it consoles its companion, it complicates lives that it enters, and it promises a form of hope. The article thus seeks to demonstrate the therapeutic capacity of stories to effect healing.
Keywords: Socio-narratology; companion story; Mattingly; Philoctetes; narrative therapy; chronic pain